First documented record of interaction between vampire bat, Desmodus rotundus (É. Geoffroy, 1810), and the Greater Naked-tailed Armadillo, Cabassous tatouay (Desmarest, 1804), Brazil - Paixão, Randson Modesto Coêlho da; Sampaio, Agnaildo de Sousa; Abraão Filho, João Carlos da Cruz; Silva, Antonio Junio Nonato da; Callado, Thomaz de Carvalho; Vargas-Mena, Juan Carlos; Salustio-Gomes, Carlos (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2025)
We reported the interaction between a common vampire bat (Desmodus rotundus) and a greater naked-tailed armadillo (Cabassous tatouay) recorded by camera traps in an Atlantic Forest remnant called ‘Mata da Sucupira Torta’ in Paraíba state, Brazil, in September 2023. This documented biological interaction corroborates the high plasticity of D. rotundus in the search for prey and underscores the urgency of understanding the processes that structure predator-prey relationships, especially in areas increasingly impacted by human activities. This observation also highlights the importance of using alternative methods to address gaps in our understanding of the ecological dynamics between predators and prey.